Determinants of Food Choices in University Cafeterias: A Cross-Sectional Study Among Public Health Students in Libya (مجلة الرازي الطبية, 2025)
Factors that influence subjects' food choices have been widely searched. However, factors that shape the food selections of university students have not been as widely assessed. It is a cross-sectional study on basic medical sciences students in the Faculty of Public Health of both sexes, carried out at the Medical Campus, University of Benghazi, in the Libyan city of Benghazi from January to June 2025. The sample size is 300 students. 6.3 % of the sample are males, and females represent 93.7 % of the total sample.  (32%) of the students live in families with 4 to 6 members. (62.69%) of the participants have family income between 1000 - 3000 Libyan Dinar (LD). Cafeteria visits and food selections were found to be significantly affected by food cleaning, food odor, price, menu, and cafeteria cleaning. Significant associations are noticed between independent variables and dependent variables at the 0.01 level.  Further research should be conducted in order to determine more specific factors that affect the food choices of college commuter students in more and different departments and faculties.